Copper-zirconia interfaces in UiO-66 enable selective catalytic hydrogenation of CO2 to methanol - Yifeng Zhu (Nature Portfolio, 2020)
Molecular interactions with both oxides and metals are essential for heterogenous catalysis, leading to remarkable impacts on activity. Here the authors show that a direct link between Cu and ZrO2 in a metal organic framework is required to hydrogenate CO2 to methanol.